An occasional series highlighting common errors that refuse to die.

“It just… won’t stay dead!” he said, as the Mathematical Zombie moved closer.

“$(a+b)^2 = a^2 + b^2$”, it said. “Brains! $(a+b)^2 = a^2 + b^2$.”

“But… it doesn’t!” he said. “You have to multiply out the brackets!”

“$(a+b)^2 = a^2 + b^2$!”

“No! $(a+b)^2 = (a+b)(a+b) = a^2 + 2ab + b^2$”, he said, firmly.

“Oh,” said the Mathematical Zombie. “So you have to write both brackets down and multiply them out? $a^2$… $ab$… another $ab$… and $b^2$… makes $a^2 + 2ab + b^2$!”

While the Mathematical Zombie was distracted, he shot it in the head.